Effects of Water Deficit Stress on Several Quantitative and Qualitative Characteristics of Canola (Brassica napus L.) Cultivars - Mohammad HOSSEINI; Payman HASSIBI (Notulae Scientia Biologicae, 2011)
Water deficit stress considered as one of the most important limiting factors for oil seed canola (Brassica napus L.) growth and productivity in Iran. To evaluate the effects of water deficit stress on some qualitative and quantitative characteristics of canola cultivars, this experiment in a greenhouse trial carried out as factorial based on completely randomized design with three replications in Shahid Chamran University of Ahwaz (Iran). Canola cultivars, including ‘Hyola 308’, ‘Hyola 401’ and ‘RGS 003’ as first factor, and the second one was three levels of water deficit stress, including stress at early stem elongation stage to early flowering (D1), early flowering stage to early emergence of sacs (D2), beginning of stem elongation stage to early emergence of sacs (D3) and normal irrigation (C, as check). Results showed that the interaction between water deficit stress and cultivars affected biological yield, seed oil yields and harvest index (p≤0.01), dry matter and economic yield (p≤0.05). Water deficit stress reduced grain oil yields. ‘Hyola 308’ under stress at beginning stem elongation stage to early flowering had the lowest oil yields (1.1 g plants-1) and ‘Hyola 401’ under non-stress conditions showed highest oil yields (4.3 g plants-1). The decrease of oil yields at the flowering stage to stem elongation stage was more than the other stages. In addition, water deficit stress reduced harvest index in the three stress levels due to reduced economic yield and reduced biological yield. Stress susceptibility index for ‘Hyola 401’ at the beginning of stem elongation stage to early emergence of sacs was 0.914 and the ‘Hyola 308’ showed 1.12 at the beginning of stem elongation stage to early emergence of sacs respectively, which it can implies that ‘Hyola 308’ is more sensitive than ‘Hyola 401’ to water deficit stress.